Diagnosis of the strategies used in the production of olive wineries in the southern region of Peru in 2020 - Mendoza Quispe, Javier Fernando (2020)
The Research topic is developed in the olive sector, the main economic activity in the Tacna region; which has experienced significant fluctuations in production, they have been due to internal aspects (low levels of productivity, product diversification, among others) and external (increased production of competing countries through incentives, optimizing processes with equipment that streamlines production and marketing policies (Business Intelligence)). The olive sector, by establishing itself as an important activity for the Region and observing the negative fluctuations and the context in which the sector is located, motivates to carry out the aforementioned research work in three stages: First Stage: Diagnosis of the Olive Processing Warehouses; which are immersed in the Association of Producers of the Yarada and the Palos that process and commercialize table olives.. Second Stage: Based on the diagnosis of the wineries and considering the demands of the international market, the application of clean production and its implication in the management of effluents are evaluated. The application of Clean Production will refer to the methodology of the “Guide for the Implementation of Cleaner Production” (GP 900.200: 2007), the same that was prepared by the Technical Committee for Standardization of Environmental Management, Sub-Committee for Production Cleaner according to R.0052-2007 /INDECOPI-CRT. Published on 2007-06-20. Tercera Etapa: Finally, a representative company that is implementing the Clean Production methodology will be identified to analyze its implications in different economic, financial, environmental, etc. In this sense, in this scientific article we will focus on the first stage of the research work. In this First Part it is concluded: Administrative management must maintain, strengthen and improve the production processes in the wineries of the Association of Producers and Marketers of Olives of Yarada and Los Palos, it is essential to guarantee continuity of production based on the sanitary, phytosanitary, environmental and quality requirements to be inserted efficiently in foreign trade and can respond to the demands of the domestic market, especially of the important retail groups in the country in order to improve their profitability and financial position..